Central Asia and Southeast Asia: towards greater engagement amidst common geopolitical challenges - Rangsimaporn, Paradorn (2023)
Central Asia and Southeast Asia share geopolitical circumstances and challenges that deserve greater policy attention in their respective interactions with powerful states impinging on regional interests. Both regions should engage with each other more to share experiences and views on how best to respond to great-power tensions and pressure.